KAWASAN INDUSTRI BERBASIS EKOLOGI - Sujiman Sujiman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
This study aims to analyze alternative priorities of the development strategy of Ecology-Based Industrial Zone (EBIZ) and a key of programe in the development strategy of the EBIZ concept. Data analysis was performed using the method of system integration experts, which AHP and ISM. Data collected in the form of secondary data (real data and hypothetical data), both quantitative and qualitative where data collection was done by using survey techniques. The manufacturing industry is one sector the largest foreign exchange earner for the national economy. However, the sector is under pressure due to the high contribution to the reduction of environmental quality and relatively high dependence on natural resources. During the manufacturing industry see the waste that it generates as a burden which if addressed fully will be able to reduce the competitiveness of the industry. Facing the challenges of the 21st century industry, came the concept of